The degenerate Carathéodory problem and the elementary multiple factor - Chernovol, N.N. (Журнал математической физики, анализа, геометрии, 2005)
The degenerate matricial interpolation Caratheodory problem is solved. To solve this problem we use the V.P. Potapov's approach based on the theory of J-expansive matrix-functions. The K-type subspace technique also plays an important role in these investigations.